(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
Photosynthetic transport was studied as an indicator of photosynthesis efficiency in two bread wheat cultivars (ACSAD 899, ACSAD 1059) under the influence of one of the salt stress. This study was carried out in sand cultures irrigated with nutrient solution in a growth chamber, and 14 days seedlings were treated with 100 mM of sodium chloride. Later the electron transport rates in those plants thylakoids were measured in 21, 28, 35 days of the experiment. Electron transport rates decreased in ACSAD 899 and reached 57% in the last day of the experiment, while it was 24.6% in ACSAD 1059. The decrease in photosynthetic electron transport rate leads to a decrease in the reduction rate of CO2 and the plant productivity as a consequence. Therefore, it could be used as criterion to express photosynthesis.